Everyday mysticism : a contemplative community at work in the desert - Glucklich, Ariel (Yale University Press, 2017)
A scholar's experiences inside a contemplative working community in Israel's Negev desert.
Keywords: Neot Smadar (Religious community); Mysticism -- Israel.; Mysticisme -- Israël.; BODY, MIND & SPIRIT -- Inspiration & Personal Growth.; BODY, MIND & SPIRIT -- Spirituality -- General.; RELIGION -- Christianity -- General.; RELIGION -- Devotional.; RELIGION -- Spirituality.; Mysticism; Israel